Single Dose versus Multiple Doses Antibiotics Prophylaxis in Patients Undergoing Elective Laparoscopic Cholecystectomy - Shrestha, Bhupendra Charan; Adhkari, Milan; Sharma, Shivraj; Shah, Dhurba Narayan; Timsina, Aliza (Annapurna Journal of Health Sciences, 2024)
Introduction: Laparoscopic cholecystectomy, a minimally invasive procedure for gallbladder removal, is favored for its reduced postoperative pain and faster recovery. However, the risk of surgical site infections (SSIs) can lead to increased morbidity and healthcare costs, necessitating effective antibiotic strategies. Methods: We conducted a prospective comparative study at Birat Medical College Teaching Hospital from 11 June 2023 to 11 September 2023. A total of 238 patients undergoing elective laparoscopic cholecystectomy were enrolled consecutively and assigned to the single dose (SD) or multiple dose (MD) group on a roll basis. The SD group received a preoperative injection of ceftriaxone (1gm) before anesthesia induction, while the MD group received plus three additional doses postoperatively, spaced 12 hours apart. Data were collected and analyzed using SPSS version 23. Results: The mean hospital stay duration was mean±SD=3.06±0.72 and 2.60±0.81 in the MD group. While patients receiving single preoperative antibiotics experienced fewer SSIs than those in the multiple dose group, there was no statistically significant association (p-value 0.775). Conclusion: This study found no significant difference in terms of surgical site infection rates between patients receiving single or multiple doses of antibiotics during laparoscopic cholecystectomy.